BANK ISLAM SEBUAH ALTERNATIF TERHADAP SISTEM BUNGA - Suyoto Arief (University of Darussalam Gontor, 2013)
This paper discusses the development of Islamic banking into an alternatives to interest-based financial institutions. In many European countries, uforia about Islamic banking already familiar. even become its own trend for the population of Europe. In economics and finance, Islamic banks generate enough decent profit. The choice to take advantage Islamic banks in the current modern economy more open to the people. However keep in mind that Islamic banks still continue to be investigated although it has been considered as an alternative. The continuity will be highly dependent on management professionalism, and support the feasibility of their business full of government and Muslims. Bank Islam has ideological advantages that allow it to offering a solution to the problem-an issue faced by Muslims and all mankind. For that we need the political will separately apply its teachings at once his willingness to carry out its renewal.